Profile of Medicolegal Cases at Department of Forensics and Legal Medicine of Dr. Hasan Sadikin General Hospital Bandung, Indonesia (Majalah Kedokteran Bandung, 2019)
The increasing number of criminal cases in Indonesia indirectly affects the number of cases handled in the Department of Forensics and Legal medicine. Forensic specialists play an important role in criminal investigation process by conducting medical examination of the corpse. This study aimed to present the profile of the corpses examined in the Department Forensic and Legal Medicine of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, during 2013-2017. This was a descriptive retrospective study based on data of the corpses examined at the Department of Forensics and Legal Medicine of Dr. Hasan Sadikin General HospitalBandung, Indonesia, in 2013–2017. During the period of study, 1,692 corpses were handled with 1,258 males (74%), 430 females (25%), and 4 with unidentified sex (1%). most of the corpses were 46–65 years old (30%) and 26–45 years old (29%) when they died. There were 24 corpses with multiple cases, making a total number of cases of 1,716 cases with an average number of cases handled each month of 29 cases. From these cases, 1,303 cases (76%) only involved external examination and 413 cases (24%) underwent autopsy (external and internal examinations). The highest number of cases was seen in 2014 (432 cases, 25%). Regarding the type of cases, Death on Arrival (DOA) cases was the most frequently seen (28%), followed by traffic accidents (26%), sudden death (22%), infanticide (7%), train accident (5%), and murders (5%). The most frequent cause of death in murder cases was sharp trauma. In conclusion, DOA and traffic accident are the dominant cases handled at the Forensics and Legal Medicine Department of Dr. Hasan Sadikin General Hospital. The high number of DOA indicates the high number of patients who come late for treatment. This needs further studies to clarify the situation in order to avoid future DOA cases. In addition, the risk factors related to the death due to traffic accidents in Indonesia need to be determined to reduce the number of fatalities in traffic accidents. Profil Kasus Medikolegal di Departemen Ilmu Kedokteran Forensik dan Medikolegal Rumah Sakit Dr. Hasan Sadikin BandungMaraknya kasus kriminal di Indonesia secara tidak langsung berefek pada jumlah kasus yang diperiksa di Departemen Ilmu Kedokteran Forensik dan Medikolegal. Dokter forensik berperan penting dalam mengungkap kasus kematian dengan melakukan pemeriksaan medik untuk kepentingan peradilan. Tujuan penelitian ini mengetahui profil kasus jenazah di Departemen Forensik dan Medikolegal RSUP Dr. Hasan Sadikin Bandung yang diperiksa selama tahun 2013-2017. Penelitian ini bersifat dekskriptif retrospektif berdasarkan data kasus jenazah yang diperiksa di Departemen Ilmu Kedokteran Forensik dan Medikolegal RSUP Dr. Hasan Sadikin Bandung tahun 2013-2017. Selama periode penelitian, terdapat 1.692 jenazah yang ditangani, terdiri dari 1.258 jenazah laki-laki (74%), 430 perempuan (25%), dan 4 jenazah (1%) tidak teridentifikasi jenis kelaminnya. Kelompok usia terbanyak adalah usia 46-65 tahun (30%) dan usia 26-45 tahun (29%). Terdapat 24 jenazah dengan kasus ganda, sehingga didapatkan total 1716 kasus, dengan rata-rata jumlah kasus setiap bulan adalah 29 kasus. Dari total kasus tersebut, yang dilakukan pemeriksaan luar saja 1.303 kasus (76%) dan yang dilakukanotopsi (pemeriksaan luar dan dalam)413 kasus (24%). Jumlah kasus terbanyak pada tahun 2014, 432 kasus (25%). Jenis kasus terbanyak adalah kasus Death on Arrival (DOA) 28%, diikuti secara berturut-turut kasus Kecelakaan Lalu Lintas 26%, Mati Mendadak 22%, Infantisid 7%, Kecelakaan Kereta Api 5% dan Pembunuhan 5%. Kasus pembunuhan terbanyak diakibatkan oleh trauma tajam. Simpulan, didapatkan kasus terbanyak pada tahun 2014 (25%), jenazah terbanyak berjenis kelamin laki-laki (76%), kelompok usia terbanyak adalah usia 46-65 tahun (30%), jenis kasus terbanyak adalah kasus DOA (28%), dan hanya 24% kasus yang dilakukan otopsi.